2018
DOI: 10.1016/j.cattod.2017.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production via aqueous-phase reforming of methanol over nickel modified Ce, Zr and La oxide supports

Abstract: Aqueous-phase reforming (APR) of methanol over nickel supported on zirconium, cerium and lanthanum oxides was performed in continuous laboratory scale reactor and discussed in this paper. The role of composition and physico-chemical properties of the supports were investigated and significant benefit of using mixed oxides CeO2-ZrO2 and La2O3-ZrO2 over the pure oxides, in term of methanol conversion and hydrogen production, was demonstrated. Methanol conversion of over 50 % with hydrogen production efficiency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…This is generally attributed to the singular redox properties of ceria (i.e., high oxygen storage capacity and oxygen mobility) which promote preferentially the WGS versus the methanation reaction and, thus, enhancing the hydrogen production [11,12]. The CeO 2 –ZrO 2, CeO 2 –La 2 O 3 and CeO 2 –TiO 2 mixed oxides have also been successfully used as support of Pt or Ni for APR, achieving a higher hydrothermal stability compared to pure CeO 2 [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This is generally attributed to the singular redox properties of ceria (i.e., high oxygen storage capacity and oxygen mobility) which promote preferentially the WGS versus the methanation reaction and, thus, enhancing the hydrogen production [11,12]. The CeO 2 –ZrO 2, CeO 2 –La 2 O 3 and CeO 2 –TiO 2 mixed oxides have also been successfully used as support of Pt or Ni for APR, achieving a higher hydrothermal stability compared to pure CeO 2 [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Shabaker et al used the Pt/Al 2 O 3 catalyst for aqueous phase reforming of methanol and ethylene glycol and demonstrated maximum activity and selectivity for hydrogen at almost 100% 74,75. AP-SRM was investigated using the Ni/25%CeO 2 − ZrO 2 catalyst, which showed more than 50% conversion of methanol and more than 40% efficiency of hydrogen 76. Cortright et al found that H 2 extraction from alcohols is possible around 227 °C via AP-SRM 77.…”
mentioning
confidence: 99%
“…The real water fraction obtained in the FT synthesis was processed in an APR reactor described elsewhere [13] over NiCu/25CeZr. Totally, 17 experiments were conducted in a down-flow, continuous, fixed-bed reactor, with inner diameter of 15 mm, where a new load of 1.5 g of calcined catalyst, without diluting it in an inert solid, was placed for each experiment for a total bed volume of 1.2 cm 3 and a bed height of 6.7 mm.…”
Section: Apr Of Ft Watermentioning
confidence: 99%
“…The first study on APR considered the process as potential for H 2 production from biomass derived compounds such as methanol, ethylene glycol (EG) and glycerol, and highlighted the need for low cost catalysts that are active at low temperatures [4]. Thereafter, a significant number of studies have been devoted to catalyst research and development to produce hydrogen in the APR of the same type of model compounds [5][6][7][8][9][10][11][12][13][14]. Additionally, a few works have focused on the APR of real water fractions derived from biorefineries [15,16].…”
Section: Introductionmentioning
confidence: 99%